Behavior Study of Top Seat Angle Steel Beam to Column Connections - Al-Fakih, Kamal Ahmed; Chin, Siew Choo; Doh, Shu Ing (Medwell Journals, 2017)
The aim of this present study was simulating the behavior of Top Seat Angle (TSA) steel connections by using Finite Element Analysis (FEA) computer software, known as "ABAQUS". The purpose of this study is to provide the basis for the fastest and most economical design and analysis and to ensure the required steel connection strength. For this study, started used review method of behavior of steel beam-to-column bolted connections. Two models of different cross-section were examined under the effect of concentrated load and different boundary conditions. In all the studied case, material nonlinearity was accounted. A sample study on TSA connections was carried out using both material and geometric nonlinearities. This object will be of great value to anyone who wants to better understand the behavior of the steel beam to column connection. The results of the study have a field of reference for future research for members of the development of the steel connection approach with simulation model design.